2011
DOI: 10.1163/092430410x547038
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Compression Effect on Filling Process in Compression Resin Transfer Molding

Abstract: The compression resin transfer molding (CRTM) filling process involves two stages: the injection phase and the compression phase. Two injection modes are considered -constant volumetric flow rate and constant pressure -while the constant compression velocity is utilized in this study. Three typical cases are used to investigate the compression initiation effects on the filling process. When the inlet condition is a constant flow rate, the numerical results show that the compression has both increase and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An exact position of the flow front versus filling time can be derived in polar coordinates. 6,7,9 For instance, the radius of the theoretical front is 78.5 mm at the injection time of 2 s and K being equal to 1.59 × 10 –9 m 2 , 28 while the average radius of the experimental front is about 74.6 mm. The deviation may result from the pressure loss in the pipelines.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An exact position of the flow front versus filling time can be derived in polar coordinates. 6,7,9 For instance, the radius of the theoretical front is 78.5 mm at the injection time of 2 s and K being equal to 1.59 × 10 –9 m 2 , 28 while the average radius of the experimental front is about 74.6 mm. The deviation may result from the pressure loss in the pipelines.…”
Section: Resultsmentioning
confidence: 97%
“…[5][6][7][8][9][10][11][12][13] Han et al 5 reported that injection/compression liquid composite molding (LCM) process could lead to more regular filling pattern and reduce the molding pressure. Chang 6 investigated the compression initiation effects on the CRTM filling process. Pham and Trochu 7 studied the effect of compression on the filling of a composite part for different compression speeds and injection pressures.…”
Section: Introductionmentioning
confidence: 99%
“…According to above study, injection compression molding has received extensive attention because it is superior to standard injection molding. [25] Specifically, injection compression molding allows lower injection pressure, shortens impregnation time due to smaller flow lengths [26,27] and reduces distortion of the fabric during injection.…”
Section: Introductionmentioning
confidence: 99%